2010
DOI: 10.1021/jf9033877
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Analysis of Water-Soluble Materials in Switchgrass

Abstract: Any valuation of a potential feedstock for bioprocessing is inherently dependent upon detailed knowledge of its chemical composition. Accepted analytical procedures for compositional analysis of biomass water-soluble extracts currently enable near-quantitative mass closure on a dry weight basis. Techniques developed in conjunction with a previous analytical assessment of corn stover have been applied to assess the composition of water-soluble materials in four representative switchgrass samples. To date, analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 17 publications
2
46
0
Order By: Relevance
“…Initially, cell density increased rapidly to ϳ2 ϫ 10 7 cells per ml, with doubling times under 3 h, likely supported by readily solubilized sugars released by abiotic thermal factors. Switchgrass typically contains approximately 15% water-soluble material, 25 to 50% of which is carbohydrate (27,28). After approximately 24 h, as the readily solubilized sugars were utilized by the bacteria, planktonic cells entered a second, slower growth phase, which was tracked over the next 200 h. During the slower growth phase, the Caldicellulosiruptor species can recruit carbohydrates by deploying extracellular, multidomain glycoside hydrolases (GHs), both free (29,30) and attached to the cell surface via the S-layer (15).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, cell density increased rapidly to ϳ2 ϫ 10 7 cells per ml, with doubling times under 3 h, likely supported by readily solubilized sugars released by abiotic thermal factors. Switchgrass typically contains approximately 15% water-soluble material, 25 to 50% of which is carbohydrate (27,28). After approximately 24 h, as the readily solubilized sugars were utilized by the bacteria, planktonic cells entered a second, slower growth phase, which was tracked over the next 200 h. During the slower growth phase, the Caldicellulosiruptor species can recruit carbohydrates by deploying extracellular, multidomain glycoside hydrolases (GHs), both free (29,30) and attached to the cell surface via the S-layer (15).…”
Section: Resultsmentioning
confidence: 99%
“…For biofuel research, determining the concentrations of sugars present in aqueous hydrolysates resulting from quantitative saccharification [1] or chemical pretreatment [2][3][4][5] of biomass is paramount to reliable technical or economic valuations of a given feedstock or conversion process. It has recently been demonstrated that knowledge of the water-soluble sugar content of biofuel feedstocks may also be important in such valuations [6][7][8]. Analytes of interest in biofuel research typically include the monomeric sugars glucose, xylose, arabinose, galactose, mannose, and fructose, as well as sucrose, maltose, and cellobiose dimers.…”
Section: Introductionmentioning
confidence: 99%
“…2C). Since the extractives include compounds, such as free sugars, oligomers, and organic acids (Chen et al, 2007;Chen et al, 2010), these compounds can be easily degraded and can potentially contribute to biogas production (Tong et al, 1990). The composition of the extractives was not analysed in this study; however, further research on the degradation of extractive compounds and their contributions to the AD process would be interesting.…”
Section: Degradation Of Substrates and Compositional Changesmentioning
confidence: 99%